2022
DOI: 10.1038/s41419-022-04761-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia-derived extracellular vesicles affect quiescence of hematopoietic stem and progenitor cells

Abstract: Patient-derived xenografted (PDX) models were generated through the transplantation of primary acute lymphoblastic leukemia (ALL) cells into immunodeficient NSG mice. We observed that ALL cells from mouse bone marrow (BM) produced extracellular vesicles (EVs) with specific expression of inducible heat shock protein HSP70, which is commonly activated in cancer cells. Taking advantage of this specific expression, we designed a strategy to generate fluorescent HSP70-labeled ALL EVs and monitor the impact of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The presence of TGF-β-related proteins as EVs cargoes has been established in cancer-associated fibroblast, epithelial to mesenchymal transition, as well as cancer metastasis [21]. Furthermore, EVs released from leukemia cells are responsible for the suppression of HSC functions through stromal reprogramming of niche-retention factors or as a consequence of leukemia EV-directed carrier delivery to HSC [28][29][30][31][32][33][34]. However, the presence of TGF-β-related proteins among leukemia-derived EVs cargoes has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of TGF-β-related proteins as EVs cargoes has been established in cancer-associated fibroblast, epithelial to mesenchymal transition, as well as cancer metastasis [21]. Furthermore, EVs released from leukemia cells are responsible for the suppression of HSC functions through stromal reprogramming of niche-retention factors or as a consequence of leukemia EV-directed carrier delivery to HSC [28][29][30][31][32][33][34]. However, the presence of TGF-β-related proteins among leukemia-derived EVs cargoes has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…injected in NSG mice, then 18 h later, cells were recovered by centrifugation at 500× g from BM, spleen and blood, debris were removed from the supernatant by centrifugation at 10,000× g . From the supernatant, UVs were isolated by pull-down, following previously described procedures [ 68 ] with a specific kit (15254394, Thermo Fisher Scientific), and analyzed by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…In detail, metabolomics studies revealed that ALL EVs were particularly rich in cholesterol, which accelerated the mitochondrial activation and promoted the loss of quiescence in targeted HSPC. This resulted in the exhaustion of quiescent healthy HSPC, confirmed by a reduced ex vivo ability of forming colonies [ 104 ].…”
Section: Mscs As Key Modulators Of Leukemia Onset Maintenance Progres...mentioning
confidence: 99%